2021
DOI: 10.1039/d1ra00955a
|View full text |Cite
|
Sign up to set email alerts
|

A 1D binary photonic crystal sensor for detecting fat concentrations in commercial milk

Abstract: Our goal in this study is to design an efficient sensor to detect the fat volume in commercial milk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…In Ref. [ 38 ], the RIs of milk samples at various fat concentrations are provided. These values are based on the experimental results and when plotted, we found that the relation between RI and concentration is not linear except for high values of concentration.…”
Section: Resultsmentioning
confidence: 99%
“…In Ref. [ 38 ], the RIs of milk samples at various fat concentrations are provided. These values are based on the experimental results and when plotted, we found that the relation between RI and concentration is not linear except for high values of concentration.…”
Section: Resultsmentioning
confidence: 99%
“… 44 These qualities make it ideal for use in high-temperature environments without compromising its optical performance. 19 In addition, GaN has been chosen for its unique optical properties (including a wide bandgap, allowing efficient operation in the ultraviolet and visible light spectrum; a high refractive index, enabling effective light confinement and manipulation crucial for enhancing biosensor sensitivity and selectivity; low optical losses essential for maintaining a high signal-to-noise ratio; and chemical stability and resistance to corrosion, making it suitable for long-term and reliable operation in biological sensing environments), 45,46 making it an ideal dielectric layer for PCB. Hence, as the constituents are arranged in a multi-layer structure, the TMM was used to model light interaction with the materials in the structure.…”
Section: Analytical Modelmentioning
confidence: 99%
“…And they reported that, the proposed sensor would be processed in a signal processing unit give an accurate estimation of the fat concentration in milk. 19 Besides, Huang et al , experimentally demonstrated an adjustable lattice orientation of 2D hexagonal PCB with thin gold film coating for Epstein–Barr virus protein detection. Their work provides a method of employing the cut-off wavelength of 2D PCB to benchmark the amount of specific bindings between antigens and antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…Based on Fano resonance, a sensor structure consisting of three parallel 1D PhC cavities is reported, and the achieved sensitivity is less than 377.2 nm RIU -1 and the detectable RI-range is around 0.05 [17]. To extend the RI range, a periodic alternating arrangement of the dielectric array is introduced in the PhC cavity and it exhibits a broad RI range of 0.36, a high Q, and a narrow FWHM of 0.2 nm [18]. However, the sensitivity reaches to a 142 nm RIU −1 which is relatively low.…”
Section: Introductionmentioning
confidence: 99%